Pengaruh Kombinasi Rebusan Bunga Rosella Dan Madu Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi Di Rt 01 Rw 02 Kp. Parung Serab Kelurahan Tirtajaya Kota Depok - Wahid Nugroho Saputra; Bambang Suryadi; Weslei Daeli (PT. Intelek Cendikiawan Nusantara, 2025)
Hypertension is a condition where blood pressure in the blood vessels is too high, with systolic blood pressure exceeding 140 mmHg or diastolic blood pressure exceeding 90 mmHg. Hypertension is often referred to as a